Radioecological Monitoring of Adjacent Territories to the Former Semipalatinsk Nuclear Test Site, East Kazakhstan - Duyssembaev, Sergazy; Serikova, Ainur; Suleimenov, Shyngys; Ikimbayeva, Nurgul; Zhexenayeva, Assel; Akhemtzhanova, Aizhan; Atambayeva, Zhibek (International Journal of Engineering and Technology, 2018)
This paper presents the results of complex radioecological monitoring of the territories, which are situated near the Semipalatinsk Nuclear Test Site, East Kazakhstan region.  The radiometric measurements showed that the concentration of radon and beta particles are below the permissible levels. EROA values of a radon in rooms fluctuates from 44 Bq/m3 to 195 Bq/ m3. The measured values of fluency of betta-particles in all the studied points are less than 10 freq/ min*cm2. A specific activity of radionuclides, such as Am-241, Cs-137 and  Pu – 239/240  in soils, plant, water, meat and milk were evaluated.